Pemanfaatan Kulit Singkong sebagai Adsorben dalam Menurunkan Kadar BOD, COD di Air Waduk Manggar Kota Balikpapan - Nia Febrianti; Vina Mauliana; Rahmi Yorika (Al-Ard: Jurnal Teknik Lingkungan, 2023)
Balikpapan City is a city that does not have a large river to supply raw water like in several other cities, so to meet the water needs of the community, the main source of raw water is obtained from surface water from the Manggar Reservoir. The presence of high amounts of organic contaminants such as BOD and COD will affect water quality if treatment is not carried out to reduce these pollutants. One of the efforts that can be made to reduce pollutant levels is by the adsorption process using natural adsorbents, namely activated carbon from cassava peels. This research was conducted to find out how the effect of mass, contact time and the effectiveness of adsorbents from activated carbon of cassava peels in reducing BOD and COD levels in Manggar reservoir water, Balikpapan City. The adsorption process was carried out using variations in mass of 1, 3, 5, 7 and 9 gr and contact time variations of 30, 45, 60, 75 and 90 minutes. Based on the results of the study, the efficiency of reducing the BOD concentration of the adsorbent of activated carbon from cassava peels was 95.06% from the initial concentration of 8.3 mg/L to 0.41 mg/L at the optimum mass of 5 grams and the efficiency of reducing the COD concentration was 100% of the initial concentration of 28.54 mg/L to 0 mg/L at an optimum mass of 3 grams with a contact time of 30 minutes. From the results of the statistical analysis tests performed, it was found that the mass variation of the adsorbent did not significantly affect the decrease in BOD and COD concentrations, while the contact time had a significant effect only on the decrease in BOD concentrations.